2019
DOI: 10.1016/j.neo.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Clodronate-Liposome Mediated Macrophage Depletion Abrogates Multiple Myeloma Tumor Establishment In Vivo

Abstract: Multiple myeloma is a fatal plasma cell malignancy that is reliant on the bone marrow microenvironment. The bone marrow is comprised of numerous cells of mesenchymal and hemopoietic origin. Of these, macrophages have been implicated to play a role in myeloma disease progression, angiogenesis, and drug resistance; however, the role of macrophages in myeloma disease establishment remains unknown. In this study, the antimyeloma efficacy of clodronate-liposome treatment, which globally and transiently depletes mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 54 publications
2
54
0
Order By: Relevance
“…At the experimental endpoint, femora and tibiae from tumor-bearing, and age- and sex-matched nontumor mice were isolated, and the BM flushed out with PFE buffer (PBS, 2% FCS, and 2 mM Ethylenediaminetetraacetic acid (EDTA)). Collagenase digestion of the cortical and trabecular bone was performed, as previously described [ 51 ]. The digested bone fragments and collagenase-isolated BM stromal cells were co-lyzed in 1 mL of TRIzol TM Reagent (Thermo Fisher Scientific) and incubated on ice for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the experimental endpoint, femora and tibiae from tumor-bearing, and age- and sex-matched nontumor mice were isolated, and the BM flushed out with PFE buffer (PBS, 2% FCS, and 2 mM Ethylenediaminetetraacetic acid (EDTA)). Collagenase digestion of the cortical and trabecular bone was performed, as previously described [ 51 ]. The digested bone fragments and collagenase-isolated BM stromal cells were co-lyzed in 1 mL of TRIzol TM Reagent (Thermo Fisher Scientific) and incubated on ice for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…For flow cytometric analysis, long bones (femora and tibiae) were excised and cleaned. Bones were gently crushed with a mortar and pestle in PFE to isolate BM and compact bone cells were isolated, as previously described [ 51 , 52 ]. Briefly, the resultant bone chips were washed, finely chopped, and incubated with 3 mg/mL collagenase type-I (ScimaR, VIC, Australia) in PBS at 37 °C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the positive outcomes obtained in MM patients with bortezomib treatment, results showed that this proteasome inhibitor also promotes the accumulation of pro-inflammatory macrophages and fosters MM cell survival and aggressiveness linked to MM disease progression, which could represent one of the mechanisms associated with MM resistance to bortezomib [ 151 ]. Moreover, depletion of macrophages or blockade of M2-polarization in murine MM models inhibits tumor growth and disease progression in vivo, and enhances survival after stem cell transplantation, providing strong evidence that macrophages are important for myeloma progression and a promising therapeutic target [ 142 , 152 , 153 ].…”
Section: Myeloid Cells Involved In MM Progressionmentioning
confidence: 99%
“…Diabetes, Metabolic Syndrome and Obesity: Targets and Therapy 2020:13 4898 for 2 weeks. 25 Every time the AFG+MD group rats injected with Lipo-Clo, the other two groups of rats would receive 100 μL of PBS solution as control.…”
Section: Dovepressmentioning
confidence: 99%